2006
DOI: 10.1016/j.electacta.2005.02.124
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation by EIS of ternary Mg alloys synthesised by mechanical alloying

Abstract: Electrochemical impedance spectroscopy has been used to study the electrochemical behaviour of ternary Mg 60 Ti 10 Si 30 and Mg 88 Ti 5 Si 7 alloy samples fabricated by mechanical alloying of the elemental powders in an argon atmosphere. The influence of different milling times up to 25 h and heat treatment on the electrochemical behaviour of the samples, after compacting under pressure into disks, has been investigated in 0.1 M Na 2 SO 4 and 0.01 M NaCl electrolyte solutions. Complementary measurements of ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 29 publications
(41 reference statements)
0
25
0
Order By: Relevance
“…The polarization curves show that both the as-cast and T6 conditions have positive corrosion potentials, while the corrosion potential of the T4 sample is negative. This indicates that corrosion potentials of the secondary phases in the as-cast and T6 samples are higher than that of the matrix and lead to an increase in corrosion potentials of the alloys, because the potential of an alloy is determined by the potential of the constituent phases and the area fraction covered by each phase [24] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polarization curves show that both the as-cast and T6 conditions have positive corrosion potentials, while the corrosion potential of the T4 sample is negative. This indicates that corrosion potentials of the secondary phases in the as-cast and T6 samples are higher than that of the matrix and lead to an increase in corrosion potentials of the alloys, because the potential of an alloy is determined by the potential of the constituent phases and the area fraction covered by each phase [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, there are two loops of the high-frequency captance and the mediumfrequency captance but without inductive loops, which shows that the low-pressure sand-cast Mg-10Gd-3Y-0.5Zr alloy has a higher resistance to pitting corrosion in different heat treatment conditions. Brett et al [24] also found that the pitting formation leads to the inductive loop in the impedance spectra. According to the studies of Makar and Kruger [25] , Cao Chu'nan [26] , and Song G. et al [27] , the bigger high-frequency capacitive loops are related to the better corrosion resistance.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 94%
See 2 more Smart Citations
“…The semicircle in high frequency region is attributed to the charge transfer or electrochemical reaction resistance (R 1 ) paralleling with double layer capacitance (CPE), and the low frequency straight line is attributed to the diffusion of hydrogen in the material bulk. Based on the circuit, the overall system ohmic resistance (R s ) and the charge transfer resistance (R 1 ) were obtained by ZView EIS fitting program in Sai software set [12,13]. CPE, which is instead of a capacitor to avoid the error arised by non-homogeneity of the system, is constant phase element which is defined by two values CPE-T and CPE-P.…”
Section: Exchange Current Densitymentioning
confidence: 99%